Analysis of symmetry in the transmission of market prices for black bean in Mexico: the cases of Zacatecas and Mexico City - González Andrade, Salvador; Aguilar López, Antonio (Acta Universitaria, 2024)
In Mexico, the dry bean (Phaseolus vulgaris) plays a leading role as a source of low-cost vegetable protein. Among the varieties available nationally, black beans represent a large proportion of the total consumption of this legume. This paper analyzes the symmetry in the price transmission of black “bola” beans in the cases of Zacatecas (main producer) and Mexico City (main consumer center). The analysis was carried out using two time series spanning from August 2005 to September 2023. Two statistical tests indicate the presence of cointegration between prices, while the results of the threshold autoregressive (TAR) and momentum threshold autoregressive (MTAR) models suggest symmetry in the speed of adjustment between prices in a long-run equilibrium relationship. The elasticity of price transmission from Zacatecas to Mexico City was estimated at 0.8627%, ceteris paribus.